Collaborative Waste Management at Tuah Serumpun Market - Susanti, Nurvi; Rasyid, Zulmeliza; Sahar, Suherman; Sari, Nila Puspita; Lusiana, Novita (Poltekkes Kemenkes Riau, 2024)
Waste management in traditional markets, particularly in Pasar Tuah Serumpun, is a challenge that requires attention from local government and the community. This study aims to analyze and identify the implementation of the Collaborative Waste Management approach in waste management at Pasar Tuah Serumpun. The method used is qualitative research with a case study design. The research informants consist of three main informants, three supporting informants, and one key informant. The research instrument employs in-depth interview guidelines. The results show that the waste separation process at Pasar Tuah Serumpun is not conducted, and the existing waste collection is inadequate. Although waste transport is carried out three times a day, the limited number of transport vehicles owned by the Siak Environmental Agency poses a major obstacle. Additionally, the temporary waste storage sites are insufficient, worsening cleanliness conditions and causing waste piles. It is hoped that relevant parties will conduct outreach on the importance of waste separation to traders and the community, build adequate and strategic temporary storage sites, increase the number of waste transport vehicles to ensure effective collection, and involve the community in waste management through collaborative programs that can enhance participation and environmental awareness.